Rapid assessment of Watson–Crick to Hoogsteen exchange in unlabeled DNA duplexes using high-power SELOPE imino 1H CEST - B. Liu; A. Rangadurai; H. Shi; H. M. Al-Hashimi; H. M. Al-Hashimi (Magnetic Resonance, 2021)
In duplex DNA, Watson–Crick A–T and G–C base pairs (bp's) exist in dynamic equilibrium with an alternative Hoogsteen conformation, which is low in abundance and short-lived. Measuring how the Hoogsteen dynamics varies across different DNA sequences, structural contexts and physiological conditions is key for identifying potential Hoogsteen hot spots and for understanding the potential roles of Hoogsteen base pairs in DNA recognition and repair. However, such studies are hampered by the need to prepare 13C or 15N isotopically enriched DNA samples for NMR relaxation dispersion (RD) experiments. Here, using SELective Optimized Proton Experiments (SELOPE) 1H CEST experiments employing high-power radiofrequency fields (B1 > 250 Hz) targeting imino protons, we demonstrate accurate and robust characterization of Watson–Crick to Hoogsteen exchange, without the need for isotopic enrichment of the DNA. For 13 residues in three DNA duplexes under different temperature and pH conditions, the exchange parameters deduced from high-power imino 1H CEST were in very good agreement with counterparts measured using off-resonance 13C /<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="3af55808dad7e355d8e0b0b2a0272ce7"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="mr-2-715-2021-ie00001.svg" width="8pt" height="14pt" src="mr-2-715-2021-ie00001.png"/></svg:svg> 15N spin relaxation in the rotating frame (R1ρ). It is shown that 1H–1H NOE effects which typically introduce artifacts in 1H-based measurements of chemical exchange can be effectively suppressed by selective excitation, provided that the relaxation delay is short (≤ 100 ms). The 1H CEST experiment can be performed with ∼ 10× higher throughput and ∼ 100× lower cost relative to 13C /<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="8pt" height="14pt" class="svg-formula" dspmath="mathimg" md5hash="265e2a7d42d09da6c1e252e5649f9787"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="mr-2-715-2021-ie00002.svg" width="8pt" height="14pt" src="mr-2-715-2021-ie00002.png"/></svg:svg> 15N R1ρ and enabled Hoogsteen chemical exchange measurements undetectable by R1ρ. The results reveal an increased propensity to form Hoogsteen bp's near terminal ends and a diminished propensity within A-tract motifs. The 1H CEST experiment provides a basis for rapidly screening Hoogsteen breathing in duplex DNA, enabling identification of unusual motifs for more in-depth characterization.